Combined reperfusion therapy to treat cryptogenic acute ischemic stroke during the first trimester of pregnancy: case report and literature review - Zhu F; Gory B; Mione G; Humbertjean L; Derelle AL; Richard S (Dove Medical Press, 2018)
François Zhu,1,2 Benjamin Gory,2,3 Gioia Mione,1 Lisa Humbertjean,1 Anne-Laure Derelle,2 Sébastien Richard1,4 1Department of Neurology, Stroke Unit, University Hospital of Nancy, Nancy Cedex, France; 2Department of Diagnostic and Therapeutic Neuroradiology, University Hospital of Nancy, Nancy Cedex, France; 3INSERM U1254, IADI F-54000, Nancy, France; 4Centre d’Investigation Clinique Plurithématique Pierre Drouin, CIC-P 1433 INSERM U1116, University Hospital of Nancy, Vandoeuvre-lès-Nancy, France Abstract: Cerebral infarction due to acute embolism in the large artery during pregnancy is a rare but severe condition threatening both the mother’s and child’s life. Physicians lack diagnostic and therapeutic guidance to manage this particular situation due to the paucity of published cases. Furthermore, the pathogeny is poorly known, rendering preventive strategies difficult. We describe the case of a young woman presenting cryptogenic acute cerebral infarction during the first trimester of pregnancy who was successfully treated with combined reperfusion therapy. We reviewed the literature to collect data about pathogeny and management. A 28-year-old pregnant woman was diagnosed with acute cerebral infarction due to left middle cerebral artery occlusion at 9 weeks of gestation. Endovascular thrombectomy combined with intravenous thrombolysis allowed cerebral reperfusion leading to a decrease in the National Institute of Health Stroke Score from 13 to 1 at 24 hours. Comprehensive etiological investigation was negative. Anticoagulation therapy with low-molecular-weight heparin was administered as preventive treatment during the pregnancy and postpartum. Neither the mother nor the child experienced any complications: the baby was born by normal vaginal delivery and the outcome was good at 1 year. We identified 21 other cases of patients treated with reperfusion therapies, four of which consisted of endovascular thrombectomy, and only one a combined strategy. Pregnant women with acute cerebral infarction due to arterial occlusion can benefit from combined reperfusion therapy. More cases should be collected to assess treatment in these patients, to understand pathogeny, and propose the best preventive strategy. Keywords: pregnancy, acute cerebral infarction, stroke, rt-PA, thrombolysis, endovascular thrombectomy